Teaching Peace and Conflict The Multiple Roles of School Textbooks in Peacebuilding - Vanner, Catherine; Akseer, Spogmai; Kovinthan Levi, Thursica (Springer International Publishing : Imprint: Springer, 2022)
XIV, 205 p. 15 illus., 2 illus. in color.